2005
DOI: 10.1086/429379
|View full text |Cite
|
Sign up to set email alerts
|

Observational Evidence of the Kink Instability in Solar Filament Eruptions and Sigmoids

Abstract: Two lines of observational evidence are used to infer that the MHD helical kink instability is associated with solar eruptions. The senses of twist and writhe are determined in images of seven erupting filaments obtained at 10830, 1600, 195, and 171 . In every case the sense of twist is the same as the sense of writhe, as required A for a kink. From images in the soft X-ray and EUV spectrum, measurements of the height/width ratio of 623 sigmoids show a mean value of 5.47, which is the ratio expected for kinke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 19 publications
(21 reference statements)
4
99
0
Order By: Relevance
“…It is very interesting that the observed helix is left-handed, which means that its sense of rotation agrees with the observed large-scale clockwise rotation of the erupting prominence. Hence, these observations give a strong support to the conversion of twist into writhe of the same sign in a kink-unstable magnetic flux-rope, as reported for instance by Rust & Labonte (2005); Zhou et al (2006).…”
Section: Discussionsupporting
confidence: 82%
“…It is very interesting that the observed helix is left-handed, which means that its sense of rotation agrees with the observed large-scale clockwise rotation of the erupting prominence. Hence, these observations give a strong support to the conversion of twist into writhe of the same sign in a kink-unstable magnetic flux-rope, as reported for instance by Rust & Labonte (2005); Zhou et al (2006).…”
Section: Discussionsupporting
confidence: 82%
“…While many erupting filaments/flux-ropes appear to kink as they erupt (e.g. Rust & LaBonte 2005;, we are aware of no conclusive observational evidence that this eruption mechanism acts on its own. Initiation by an MHD instability without any field weakening by reconnection could be proved by observations of strong-field filament eruptions in which the impulsive phase is observed prior to any sign of X-ray or EUV brightening in the active region.…”
Section: Discussionmentioning
confidence: 91%
“…Moore & Roumeliotis 1992), external tether-cutting or "breakout" (Antiochos 1998;Antiochos et al 1999), or the flux cancelation model originally proposed by van Ballegooijen & Martens (1989) and further investigated by Linker et al (2003). Other models of filament eruptions include the kink instability of the filament/flux rope (Fan 2005;Rust & LaBonte 2005;. These models can be distinguished from each other mainly during the eruption initiation; they all tend to look the same during the eruption impulsive phase.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of sigmoids being part of a kinked flux rope was supported by estimating the deformation of the kinked rope, which gave values consistent with the range observed for sigmoids (Török et al 2004). Observations of filament eruptions strongly suggested that a helical kink in flux rope topology was present (Ji et al 2003;Rust & LaBonte 2005;Williams et al 2005;Alexander et al 2006). Zhou et al (2006) described a clear case of two successive coronal mass ejections driven by the kink instability of an eruptive prominence.…”
Section: Introductionmentioning
confidence: 76%